Mengintegrasikan permainan tradisional dengan permainan edukatif untuk memahami dan meningkatkan pemahaman permainan di kalangan siswa sekolah dasar. - Uray Gustian; Baiq Satrianingsih; Intan Primayanti (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Students' academic ability can be improved through integrated learning activities of physical activity and actual gameplay. However, many teachers still have difficulties implementing it in physical education learning. The study investigates the effectiveness of the Teaching Games for Understanding (TGfU) model, implemented through modified Kasti games, in enhancing game understanding among elementary students. Conducted as a pre-experimental study with a one-group pretest-posttest design, it involved 48 fifth-grade students in West Kalimantan, Indonesia. The intervention spanned five sessions and assessed game understanding through the Games Understanding Assessment Instrument (GPAI), focusing on decision-making, skill execution, and covering. Results showed a significant improvement in post-test and post-test scores, with marked progress in each assessed component. The study highlights TGfU's potential in fostering tactical and cognitive skills in physical education for young learners, suggesting that traditional games adapted within this model offer a culturally relevant and effective approach to increasing students' engagement and understanding. Limitations include the absence of a control group and a small sample size, recommending further research to confirm these findings in diverse educational settings.